2013
DOI: 10.1016/j.psychres.2013.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of cognitive impairments in psychotic disorders: A population-based study

Abstract: Cognitive deficits have been found to be more prevalent in psychotic than in other disorders. Longitudinal research has shown that these deficits were generally already existent before onset of illness and are therefore not necessarily attributable to neurodegenerative processes. This study investigated whether both low IQ and markers of premorbid cognitive dysfunction independently contribute to an increased risk for psychoses. In a cross-sectional study about 50,000 young Swiss males completed a survey of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…During baseline testing, our sample group of 'true' at-risk individuals with later conversion was exhibiting significantly lower performances on the domains of processing speed, fluency, learning/memory, and working memory, as well as a lower estimated pre-morbid IQ. Thus, our results may confirm the assumption that neurocognitive deficits are present prior to the development of psychosis Giuliano et al 2012;Fusar-Poli et al 2012a;Müller et al 2013;Bora et al 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…During baseline testing, our sample group of 'true' at-risk individuals with later conversion was exhibiting significantly lower performances on the domains of processing speed, fluency, learning/memory, and working memory, as well as a lower estimated pre-morbid IQ. Thus, our results may confirm the assumption that neurocognitive deficits are present prior to the development of psychosis Giuliano et al 2012;Fusar-Poli et al 2012a;Müller et al 2013;Bora et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Some researchers have critically questioned whether schizophrenia is inherently progressive and have suggested that the disability may result -unless referral and sampling biases exist -from stable deficits that are established before the onset of the illness Bora & Murray, 2013;Zipursky et al 2013). In line with a neurodevelopmental model of schizophrenia, recent studies have provided evidence that cognitive and intellectual deficits are apparent early in neurodevelopment, several years before the onset of psychosis Giuliano et al 2012;Fusar-Poli et al 2012a;Müller et al 2013;Bora et al 2014). Birth cohort and conscript studies report strong associations between poor performance on cognitive batteries and increased risk of later schizophrenia (MacCabe, 2008;MacCabe et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to the neurodevelopmental hypothesis of pathogenesis in schizophrenia, along with recent findings, neurocognitive deficits are most likely to be present prior to the manifestation of full-blown schizophrenia (Giuliano et al 2012). This supposition is also supported by a recent large population study of young Swiss conscripts by Müller et al (2013), who found significantly frequent evidence of cognitive impairments early in life for individuals who were later diagnosed with schizophrenia. Therefore, an assessment of cognitive functioning should be taken into account in early detection of psychoses.…”
Section: Introductionmentioning
confidence: 52%
“…Various ensuing studies replicated those cognitive deficits prior to the onset of full-blown psychosis (e.g., MacCabe et al, 2008;MacCabe et al, 2013;Metzler et al, 2014;Müller et al, 2013;Reichenberg et al, 2010;Zammit et al, 2004). Broad scientific consensus now exists among experts that poor premorbid cognitive functioning is a risk factor for schizophrenia and other psychotic disorders (Khandaker et al, 2011;MacCabe, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We are unaware of further reports about cognitive deficits that are separated by sex in those phenotypes. Many conclusions about premorbid cognitive functioning in psychosis have been drawn exclusively from male samples (e.g., MacCabe et al, 2013;Müller et al, 2013;Zammit et al, 2004). None of the studies focusing on the extended psychosis phenotype have examined potential sex differences.…”
Section: Introductionmentioning
confidence: 99%